Interplay between antipredator behavior, parasitism, and gut microbiome in wild stickleback populations - Javier Edo Varg; Jaelle C. Brealey; David Benhaïm; Rafael Losada-Germain; Janette W. Boughman (npj Biofilms and Microbiomes)
Abstract The impact of microbial composition on stress-related behavior in aquatic organisms is poorly understood. This study explored the link between antipredator behavior, parasitism, and the gut microbiome in wild stickleback from two lakes: clear, spring-fed Galtaból and turbid, glacial-fed Þristikla. Behavioral analysis revealed differences between populations, with each exhibiting unique baseline behaviors. Microbiome analysis showed that a small proportion of its variation was explained by population, likely reflecting differences in lake environments. Only the marine genus Pseudoalteromonas abundance differed between populations. Our findings suggest that behavior and microbiome correlations may primarily reflect environmental adaptations and parasite status rather than direct gut-brain interactions. However, some tentative evidence suggests a potential innate connection between some antipredator behavior and microbiome composition. The study highlights the complexity of the gut-brain axis in wild populations and suggests future research directions, including experimental manipulations to uncover causal relationships between microbiome composition and behavior.